Emotional intelligence of Malaysian university students using non-parametric approach - Mohd Razali, Siti Noor Asyikin; Tan, Pei Chy; Khamis, Azme (Universiti Malaysia Perlis (UNIMAP), 2018)
The purposes of present study are to investigate the level of emotional intelligence among university students, identify the significant differences of emotional intelligence with demographic background and measure the relationship of emotional intelligence with academic performance. Non-parametric methods which are Mann-Whitney test, Kruskal-Wallis test and Spearman Correlation test were used to analyze 400 data from eight different faculties. Results found that the level of emotional intelligence among university students is at average or above level. The different of age, ethnic, faculty, hometown location and family income have significant difference in emotional intelligence. Besides that, there are strong positive relationship between emotional intelligence and academic performance among university students.